Pengaruh Penyekatan Kanal Terhadap Pembasahan Lahan Gambut (Studi Kasus: Desa Dompas, Kabupaten Bengkalis) - Muhammad Randy Alfath; Rinaldi Rinaldi; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Peatland fire often occur in Indonesia. One of the causes was because of the ground water level (GWL) decreased due to many canals. Some efforts that can be done are by rehabilitating peat’s ecosystems. The Peat Restoration Agency (BRG) has implemented a peat restoration effort, such as rewetting activities (rewetting of peatlands) by building canal blocks. Dompas village is a peat area and has the potential to experience a fire during the dry season. The installation of canals were expected to increase the peat water level in accordance with the provisions of less or equal to 40 cm from the ground surface. In this study the analysis of the impact of canal blocking was using Deep well media to determine changes in peat water level due to canal blocking. Four deep wells were installed at 4 transects, and each transect had 4 deep wells installed with the provisions of 1 transect downstream and 3 transects upstream. The analysis was carried out before and after the canal was blocked to find out how much influence the canal blocking had on wetting the peat land. The installation of canals in this study was able to raise the GWL by 10 cm to 21 cm with a wetting distance further than 75 meters from the canal. Keywords : peatland fires,rewetting, canal blocking, deep well.